Pengembangan Media Pembelajaran Berbasis Website Pada Mata Pelajaran Dasar Teknik Elektronika untuk Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan - Amelda Amartha; Bagus Dwicahyono; Endi Permata (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to enhance the academic performance of vocational high school students in the Basic Electronic Engineering course through the development of a valid, practical, and effective web- based learning platform. Employing a Research and Development (R&D) methodology, the research utilized the 4D instructional design model, which encompasses the Define, Design, Develop, and Disseminate phases. The research subjects comprised 29 tenth-grade students enrolled in the Electrical Power Installation Engineering vocational program. Data were gathered utilizing pre-test and post- test assessments, supplemented by expert validation and feasibility questionnaires. According to Aiken’s V index calculations across material, construct, and linguistic aspects, the developed instrument demonstrated a remarkably high level of validity. Furthermore, evaluations conducted by subject-matter and media experts classified the product as "Highly Feasible." Regarding instructional effectiveness, student outcomes exhibited a significant improvement, with average scores rising from 55.9 in the pre-test to 82.5 in the post-test. The calculated N-Gain score stood at 0.603, falling into the "Moderate" category. In conclusion, the developed web-based instructional media is authentic, highly practical, and reliable for elevating students learning achievements.